2021
DOI: 10.1371/journal.pone.0253765
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive versus liberal fluid resuscitation strategy, influence on blood loss and hemostatic parameters in mild obstetric hemorrhage: An open-label randomized controlled trial. (REFILL study)

Abstract: Background Evidence for optimal hemostatic resuscitation in postpartum hemorrhage (PPH) is lacking. Liberal fluid administration may result in acidosis, hypothermia and coagulopathy. Objective We hypothesize that in early PPH a restrictive fluid administration results in less progression to moderate PPH. Study design In four Dutch hospitals we recruited women of 18 years and over, and more than 24 weeks pregnant. Exclusion criteria were: anticoagulant therapy, known coagulation disorders, pre-eclampsia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Especially volumes greater than 4l of crystalloids and colloids are associated with increased adverse maternal outcomes 845 . A restrictive resuscitation with crystalloids appears to be equal to a liberal strategy in mild PPH 846 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Especially volumes greater than 4l of crystalloids and colloids are associated with increased adverse maternal outcomes 845 . A restrictive resuscitation with crystalloids appears to be equal to a liberal strategy in mild PPH 846 …”
Section: Discussionmentioning
confidence: 98%
“…845 A restrictive resuscitation with crystalloids appears to be equal to a liberal strategy in mild PPH. 846 Platelet count Low platelet count is associated with increased risk of severe PPH, RBC and FFP transfusion. [847][848][849][850][851][852] Mild prepartum thrombocytopenia (<150 Â 10 9 l À1 ) and lower platelet counts are associated with gradually increasing risk of severe PPH following vaginal delivery and caesarean section.…”
Section: Evidence Summarymentioning
confidence: 99%
“…As pointed out through the study conducted by 4 Cesarean section is a bloody procedure; between 750 to 1000 mL of blood are lost during most operations, and over 1000 mL of blood must be lost in order for the patient to be classified as having a postpartum haemorrhage (PPH). 13 The aim of our study is to study, investigate, evaluate the effect of changed surgical gloves post placental delivery intra -operative cesarean section versus usual care.This randomized controll study was conducted in the obestetric ward of Al Hussin Hospital to estimate the effect of intra-operative glove changing during cesarean section on postoperative complication(clinical trial).…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive fluid administration was defined as clear fluids at 0.75 to 1.0 times the volume of blood lost, and liberal fluid administration was clear fluids at 1.5 to 2.0 times the volume lost. The authors found that there was no statistical difference between progression to blood loss greater than 1000 mL, need for blood transfusion, alteration in coagulation parameters, or adverse events between the 2 groups 57…”
Section: Risk Factorsmentioning
confidence: 96%
“…The authors found that there was no statistical difference between progression to blood loss greater than 1000 mL, need for blood transfusion, alteration in coagulation parameters, or adverse events between the 2 groups. 57…”
Section: Pregnancy-related Factorsmentioning
confidence: 99%